Analysis Of Worker Nutrition And Workload With Fatigue Levet At SPBE PD Bumi Wiralodra Indramayu (PD BWI) Year 2020 - Marhatun Solehah; Tating Nuraeni; Tayong Siti Nurbaeti (Cleanliness: Journal of Health Sciences and Medical Research, 2024)
Fatigue at work is one of the health and safety problems that can be a risk factor for accidents at work. Fatigue can be influenced by many factors, one of which is excessive nutritional intake and heavy workload. This study aims to determine the analysis of nutritional intake and to determine the relationship between nutritional intake and workload with fatigue levels in SPBE PD. Bumi Wiralodra Indramayu. This type of research is an analytic observational study using a cross sectional design. The sample in this study were workers at SPBE PD. Bumi Wiralodra Indramayu as many as 36 respondents. The analysis used was the chi square test. The results of this study indicate that: There were 24 respondents (66.7%) who felt tired and 12 (33.3%) who felt not tired. Respondents who had more nutritional intake were 33 people (91.7%) and those who felt that they had less nutritional intake were 3 people (8.3%). Respondents who have heavy workload are 16 people (44.4%) and respondents who have light work are 20 people (55.6%). There is no relationship between workers' nutritional intake and fatigue level with a P-value of 0.359. There is a relationship between workload and fatigue level with a P-value of 0.003. Companies are expected to pay more attention to working hours for workers, especially in the production section, so that no workers do work outside of operational hours.